Penerapan Model Pembelajaran PBL untuk Meningkatkan Kemampuan Komunikasi Matematis Siswa Kelas X MP 1 di SMK Negeri 6 Medan - Rizki Aprina Nuranti; Surya Wisada Dachi; Elfira Handayani (Departement of Mathematics Education, 2024)
The purpose of this study was to determine the increase in students' mathematical communication abilities through the application of problem based learning (PBL) on statistics matter. The subjects in this study were class X MP 1 at SMK Negeri 6 Medan, which consisted of 32 students. Data was collected through observation and test methods. The type of research used was classroom action research (CAR), which consisted of 2 cycles where each cycle was conducted in 2 meetings. Before being given an action, students are given an initial test and at the end of the cycle students are given a test to measure their mathematical communication ability after being given an action. Classically, it was found that 5 students (15,625%) succeeded in solving problems in the initial test, 16 students (57,83%) succeeded in solving problems in test I and 30 students (93,75%) succeeded in solving problems in test II. The research results show that the application of the problem based learning can improve students' mathematical communication abilities